Population Pharmacokinetics of Tenecteplase in Patients With Acute Myocardial Infarction and Application to Patients With Acute Ischemic Stroke. (23rd November 2022) - Tang, Fei; Langenhorst, Jurgen; Dang, Steve; Kassir, Nastya; Owen, Ryan; Purdon, Barbara; Magnusson, Mats O.; Deng, Rong
Abstract: The pharmacokinetics (PK) of tenecteplase in patients with acute ischemic stroke has not been extensively studied. This study aimed to describe PK characteristics of tenecteplase in patients with acute myocardial infarction (AMI) using a population PK approach and to assess applicability of the findings to patients with acute ischemic stroke by means of external validation. A population PK model was developed using nonlinear mixed‐effects modeling based on the phase II TIMI 10B study in patients with AMI (785 PK observations from 103 patients). The statistical and clinical impact of selected covariates on PK parameters were evaluated by a stepwise covariate modeling procedure and simulations, respectively. The performance of the final model was evaluated for patients with acute ischemic stroke using summary statistics of tenecteplase concentrations of 75 patients from investigator‐initiated study N1811s. Tenecteplase PK was well described by a 2‐compartment linear model, incorporating allometric scaling of clearance and volume parameters and weight‐normalized creatinine clearance on clearance. Simulations showed that the identified covariates (weight and creatinine clearance) were of limited influence on exposure at the intended dosing regimen for patients with acute ischemic stroke. The model overpredicted mean tenecteplase plasma concentrations from N1811s by 39%, but 72% of the distribution from N1811s was within the 90% prediction interval of the model predictions. The PK characteristics of tenecteplase in patients with AMI were well described by the final model. Simulations from the model indicated that no specific dose recommendations based on covariates are warranted for patients with AMI.